2016
DOI: 10.1038/nphys3966
|View full text |Cite
|
Sign up to set email alerts
|

Propagating compaction bands in confined compression of snow

Abstract: We show that the plastic deformation of snow under uniaxial compression is characterized by complex spatio-temporal strain localization phenomena. Deformation is characterized by repeated nucleation and propagation of compaction bands. Compaction bands are also observed during the very first stage of compression of solid foams where a single band moves across the sample at approximately constant stress. However, snow differs from these materials as repeated nucleation and propagation of bands occurs throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 26 publications
6
66
0
Order By: Relevance
“…These discoveries have opened a new field of research into 'crunchy matter' [5], i.e., porous, brittle media, composed predominantly of voids. Since then, similar compaction patterns have been witnessed in snow [6].…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…These discoveries have opened a new field of research into 'crunchy matter' [5], i.e., porous, brittle media, composed predominantly of voids. Since then, similar compaction patterns have been witnessed in snow [6].…”
mentioning
confidence: 68%
“…We question whether strain-rate softening, as has been observed experimentally at the bulk sample scale in snow [6,21,22], is a necessary condition for obtaining dynamic instability patterns in brittle porous media. To address this point, we seek a model that can capture strain-rate softening as an emergent phenomenon from microstructural properties.…”
mentioning
confidence: 99%
“…The elastic modulus of snow is a fundamental mechanical property relating stress and strain. It is a highly relevant parameter for many snow mechanical application covering engineering aspects of tire traction (Choi et al, 2012), interpretation of seismic waves (Diez et al, 2015), snow fracture in relation to avalanche release (Van Herwijnen et al, 2016), or the validation of new constitutive models (Barraclough et al, 2017). Snow is a fragile, porous material that exists close to its melting point, making it highly rate dependent with a strong microstructural influence.…”
Section: Introductionmentioning
confidence: 99%
“…A first support for this generic claim is given in the Supplementary Information, which shows similar predictions for alternative force dissipation mechanisms (namely, similar patterns arise when one employs local damping or friction instead of global damping). A second support is given by comparing model simulations with experiments; this time on dry foamy snow, given by Barraclough et al 6 (see Fig. 2g,i), who adopted an experimental configuration similar to that of Valdes et al 5 (shown in Fig.…”
mentioning
confidence: 99%
“…phenomenological continuum model for snow, with an assumed elastoplastic yield function, power-law density dependence, shearinduced bond failure, strength recovery due to sintering, and nonlocality of damage 6 . The need for these assumptions indicates that the underlying mechanisms that control the emergence of oscillatory compaction bands are not clear yet.…”
mentioning
confidence: 99%